From the Education Paradox to Climate Challenges: An Institutional Analysis of Rural Women's Empowerment in the Jordanian Agricultural Sector - Al-Rkebat, Rasha Ahmad (Arab Journal for Sciences and Research Publishing, 2025)
This study aims to provide a systematic institutional analysis of the persistent gap between the high educational attainment of Jordanian women and their low level of economic participation, a phenomenon commonly referred to as the “Jordanian Paradox.” The analysis focuses specifically on rural women in the agricultural sector, who face intersecting institutional and environmental constraints that are further intensified by the accelerating impacts of climate change. The study adopts a descriptive–analytical approach that integrates quantitative and qualitative data, drawing on an integrated theoretical framework combining the Social Relations Approach and the Capability Approach. Quantitative analysis is based on data from the Labor Force Survey (LFS) and the World Bank Enterprise Survey (WBES), alongside the proposal of an innovative methodology—the Geo-Institutional Principal–Agent Analysis (GIPA)—to incorporate spatial environmental and institutional constraints into economic modeling. The findings indicate that women’s low economic participation is driven by multidimensional structural constraints that are particularly pronounced in rural contexts. WBES data reveal that women-led enterprises are significantly less likely to obtain commercial credit due to collateral requirements, reflecting patterns of indirect discrimination. These challenges are further compounded by limited provision of public resources and increasing water scarcity. The study concludes that addressing the Jordanian Paradox requires transformative reforms that directly target institutional constraints through an integrated approach linking economic empowerment, food security, and climate adaptation, with a focus on rights, access to resources, and representation.
Keywords: Women's Empowerment; Rural Women; Agricultural Sector; Climate Change; Jordanian Paradox; Capability Approach; Institutional Constraints